Darbo rinkos informacinis aprūpinimas: informacijos mokslo požiūris - Stonkienė, Marija (Information & Media, 1996)
The investigated object of the work market's information supply of Lithuania is considered to be problems of the formation of the surroundings for work market subjects.While investigating work market's information supply, it is purposeful to apply methodical regulations of information science. The information supply of the Lithuanian work market is being realised at two levels, the macro level and the local level. The information supply at the local level more strongly influences the parameters of the current work market. The basis of realisation of this information supply is informatized business, i. e., communication. In informatized business, like communication of work market's information supply, information systems of several types interact: generation of information, change of information, protection of information, and spreading of information.